مسوغات تفضيل الزوجة والأولاد في العطية: دراسة فقهية مقاصدية - عبد، هيثم حازم (جامعة الموصل - كلية العلوم الإسلامية, 2021)
هذا البحث يسلط الضوء على مجموعة من النوازل الفقهية ذات البعدين القديم والمعاصر، فهي من النوازل التي يكثر السؤال عنها، قديما وحديثا، ومن أهمها، عطية بعض الأولاد وحرمان الأخرين في حياة الأب، فيعالج الباحث هذه القضية الخطيرة على واقع أسرنا من بعدين: بعد فقهي: وبعد مقاصدي، وصولا إلى الرأي الذي يرجحه وفق حاجات الناس ومصالحهم، مع مراعاة الجانب الشرعي، كما يناقش قضية تفضيل الزوجة على العاصب النسبي، فحينما لا يكون للزوج ذرية من الذكور يلجئ الزوج إلى تسجيل بعض أملاكه (كبيت السكن) باسم الزوجة لصيانتها من بعده، فيعالج الباحث ذلك من جانب فقهي مقاصدي، ليجيب على التساؤلات ويزيح الإشكاليات، وصولا إلى الرأي الذي يرجحه فيها مراعيا مقصد العدل ودفع الضرر عن جميع الجهات المستفيدة من قضية الإرث، كل ذلك وفق نظرة شرعية مقاصدية.
For you to highlight the time on a group of jurisprudential issues of old and contemporary dimensions, as they are among the functions that are frequently asked about, in the past and present, and among the most important ones is the gift of some children and the deprivation of others in the love of the father, so the researcher deals with this serious issue on our families from two dimensions: after Fiqh: After my misfortunes, up to the opinion that is favored by the needs and interests of people, taking into account the Sharia computing, he also discusses the principle of detailing the soul over the games of forgetting. After him, the investigator deals with this on the part of a jurist who disparages me, in order to find him in the shawls and relieve the problems, and one time the one who thinks that he is more likely to take care of it with the mind and benefit the ale from all the parties benefiting from the inheritance intention, all according to a legitimate view of intent
Keywords: الشريعة الإسلامية -- الفقه الإسلامي -- النوازل الفقهية -- الجوانب الفقهية -- الدراسات الفقهية